Application of MgO/ZrO2 coating on 309 stainless steel to increase resistance to corrosion at high temperatures and oxidation by an electrochemical method - Zeydabadi-Nejad, Hassan; Bazargan-Lari, Reza; Memarzadeh, Raheleh (High temperature materials and processes, 2024)
309 stainless steel is one of the steels that have the highest resistance to corrosion and thermal oxidation compared to other steel grades, but it should not be used at temperatures higher than 980°C if there are temperature fluctuations. Additionally, 309 stainless steel is not designed for use in wet environments and has the least corrosion resistance. This study aims to cover 309 stainless steel with MgO/ZrO particles using a two-step electroplating deposition method and then sintering to increase its resistance to wet corrosion and oxidation in temperature fluctuations. The intermediate ZrO coating makes the outer MgO layer about two times thicker and reduces the corrosion current density. The morphology of the coatings was determined using scanning electron microscopy and X-ray diffraction, and oxidation resistance was determined using cyclic oxidation tests and the wet corrosion test of the corrosion solution. 3.5% NaCl was used. The results showed that the coated samples, due to the use of TiO middle layer and MgO protective layer in the electrochemical method, have a 2-fold increase in wet corrosion and an increase in hardness of about 77%, as well as an increase in oxidation resistance of 1.8% compared to the sample without coating. Also, the reason for using the electrochemical deposition method is for better surface smoothness and less porosity of the coating as well as its use on all metals compared to thermal spray methods.